ORIENTASI PENDIDIKAN ISLAM PADA ERA MILENIAL - Masdub, Masdub (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2023)
Millennials are the younger generation who were born between the 1980s and 2006. Millennials were born where the modern world and advanced technology were introduced to the public, when color TV, cellphones and the internet already existed, and of course have some habits and characteristics of their own from previous generations. On average among Indonesian youth, they are familiar with and use the internet in their daily lives. However, most of them have not been able to distinguish between positive and negative internet activities, and tend to be easily influenced by their social environment in their use. Islamic education is education based on Islamic teachings (Qur'an and Sunnah), namely an activity of guidance and care for students so that later after completing their education they will be able to understand, live and then believe as a whole, then these Islamic teachings are used as a principle of view. his life for the sake of physical and spiritual safety and well-being later towards the happiness of the world and the hereafter. Islamic education places great emphasis on noble character, which must be possessed by people in the millennial era, character that is moderate militancy, that is adhering to the teachings of the Shari'ah as stipulated in the Qur'an and al-Sunnah, but in its implementation it can collaborate with ethics, morals , manners, culture and customs. In addition to being able to use the instructions of the Qur'an and al-Sunnah, especially the success of the Prophet Muhammad, he can also take inspiration from what other nations in the world have done.